Application of Problem-Based Learning Model to Improve Students' Understanding of Legal Protection for Female Workers - Mulyadi Mulyadi; Sutarman Yodo; Chulbana Chulbana; Hasia Marto (CV. Global Cendekia Inti, 2026)
This study analyzed the effectiveness of implementing the Problem-Based Learning (PBL) method in improving students' critical thinking skills and understanding of labor law courses, particularly the material on legal protection for female workers. The transformation of the contemporary legal education paradigm required a shift from a teacher-centered approach to student-centered learning that developed students' critical analysis skills. The research used a Classroom Action Research design with a qualitative-quantitative approach involving 32 students from the Law Study Program at Madako Tolitoli University in the fourth semester of 2024. The research was conducted in two learning cycles following the stages of planning, implementation, observation, and reflection. Data collection instruments consisted of structured observation sheets, critical thinking assessment rubrics covering six dimensions interpretation, analysis, evaluation, inference, explanation, and self-regulation and semi-structured interview guides, analyzed using a mixed-methods sequential explanatory design. The results showed a significant increase in students' critical thinking skills of 55.2% from the first cycle to the second cycle, with the average score rising from 2.48 to 3.85, and 87.5% of students achieved the good category, exceeding the established success indicators. The PBL method facilitated collaborative learning that developed multidimensional perspectives and metacognitive skills essential for professional legal practice. These findings confirmed social constructivism theory and contributed significantly to pedagogical innovation in legal education.